Respostas

2014-06-03T21:43:33-03:00
x² + 3x - 4 = 0
a = 1
b = 3
c = -4
       
Δ = b² - 4ac
       Δ = 3² - 4 . 1 . (-4)
       Δ = 9 + 16
       Δ = 25
                x = - b ± √Δ / 2a
                x = - 3 ± √25 / 2 . 1
                x' = - 3 + 5 / 2 = 2 / 2 = 1
                x'' = - 3 - 5 / 2 = -8 / 2 = -4
As raízes da equação são -4 e 1.

Espero ter ajudado. Valeu!
1 5 1
2014-06-03T22:08:11-03:00
Valores: a=1    b=3     c=-4
Δ=b²-4.a.c
Δ= 3²-4.1.(-4)
Δ=9+16
Δ=25

x= -b±√¯ Δ
        2.a
x=-3±√¯25
     2.1
x=-3±5
     2
x1=-3-5 -8 -4
      2       2  

x2=-3+5
 +21
       2       2    

S={-4;1}